Platelet-Rich Plasma Regenerative Medicine: Sports Medicine, Orthopedic, and Recovery of Musculoskeletal Injuries - Lana, José Fábio Santos Duarte; Andrade Santana, Maria Helena; Dias Belangero, William; Malheiros Luzo, Angela Cristina (Lecture Notes in Bioengineering, 2014)
Platelet-Rich Plasma (PRP) has gained tremendous popularity in recent years as a treatment option for specialties including Orthopedics, Dentistry, Sports Medicine, Otorhinolaryngology, Neurosurgery, Ophthalmology, Urology, Vascular, Cardiothoracic and Maxillofacial Surgery, and Veterinarian Medicine. Nowadays, PRP and Stem Cell Science have added an exciting dimension to tissue repair. This book begins by giving the reader a broad overview of current progress as well as a discussion of the technical aspects of preparation and therapeutic use of autologous PRP. It is followed by a review of platelet structure, function and major growth factors in PRP (PDGF and TGFβ).The third chapter outlines the basic principles of biochemical cellular metabolism that increases the efficacy of PRP. Analogous to the preparation of soil for a garden, restoring cellular health should be the first consideration in Regenerative Medicine. Standardization of PRP preparation to clinical use still remains a challenging prospect. In this sense, a feasible strategy for studying PRP preparation is illustrated, which also allows to modulate and tailor the quality of PRP for further clinical applications. The science behind PRP and stem cells, on tissue regeneration, cell proliferation and mesenchyme stem-cells are emphasized and reviewed. Various specific uses of PRP are described with detailed illustrations of various personal experiences mainly in orthopedic injuries, ligament and tend on repair, degenerative diseases, sports medicine, chronic wound healing as well as rehabilitation aspects in tendinopathy. Expertly written by leading scientists in the field, this book provides for beginners and experienced readers scientific fundamentals, the state of art of PRP, specific uses and personal experiences with a practical approach and reference for current trends in use. Finally, this book paves the way for future developments.